Posthemorrhagic Ventricular Dilatation—Impact on Early Neurodevelopmental Outcome - Srinivasakumar, Preethi; Limbrick, David; Munro, Rebecca; Mercer, Deanna; Rao, Rakesh; Inder, Terrie; Mathur, Amit (American Journal of Perinatology, 2013)
Objective This study evaluates the impact of ventricular dilatation following severe (grades III or IV) intraventricular hemorrhage (IVH) in preterm neonates and the current practice of neurosurgical interventions in infants with posthemorrhagic ventricular dilatation (PHVD) and early neurodevelopmental outcome.Study Design Premature neonates born at ≤34 weeks' gestational ages with severe IVH were identified retrospectively over a 5-year period (2005 to 2009). Standard measures of ventricular dilatation on head ultrasound (HUS) were recorded. The treatment of PHVD, timing of surgery including the type of temporizing neurosurgical procedure (TNP)—either a ventricular reservoir or a subgaleal shunt—and the subsequent need for ventriculoperitoneal (VP) shunt were evaluated. Patients were retrospectively stratified to an “early” versus “late” intervention group based on HUS measures. Early intervention was defined as TNP performed when the ventricular index (VI) was >97th percentile but <97th percentile + 4 mm. Late intervention was defined as TNP performed when VI was ≥97th percentile + 4 mm. Neurodevelopmental outcomes were evaluated at 18 to 24 months. Infants followed up for neurodevelopmental testing were stratified as group A (progressive PHVD with TNP), group B (PHVD without TNP), and group C (severe IVH without PHVD).Results One hundred seventy-three preterm neonates with severe IVH were identified during the study period, of whom 139/173 (80%) developed PHVD. Of these, 54 (54/139, 39%) received TNP either early (4/54, 7%) or late (50/54, 93%). Of those who received TNP, 32/54 (59%) required subsequent VP shunt placement. Neurodevelopmental testing was available in 39/109 (36%) infants who survived to discharge. The mean ± standard deviation cognitive, motor, and language composite scores were 77 ± 14.8, 67 ± 15.2, 70 ± 13.8 for group A (n = 16/39), 90 ± 7.8, 84 ± 9.6, 82 ± 18.2 for group B (n = 12/39), and 95 ± 14.3, 86 ± 10.7, 94 ± 15.8 for group C (n = 11/39), respectively (p < 0.006 for group A versus group B and p < 0.004 for group A versus group C across all domains). Increasing ventricular dilatation was associated with adverse motor, cognitive, and language outcomes (p = 0.002) and neonates with progressive PHVD requiring a TNP were most adversely affected (p = 0.0006). There were no differences in any outcome measures between the two types of TNPs. Clinical and demographic characteristics of infants lost to follow-up were not significantly different than those available for follow-up.Conclusion Increasing ventricular size adversely affects neurodevelopmental outcome in infants with PHVD.
Keywords: intraventricular hemorrhage; posthemorrhagic ventricular dilatation; head ultrasound; ventricular index; temporizing neurosurgical procedure; ventricular reservoir; subgaleal shunt